Grupa społeczna jako obraz własnej tożsamości: spektrum autyzmu w zwierciadle – układanka tożsamości - Feingold Enav, Tamar (Studia Edukacyjne, 2018)
From a social-cognitive perspective, how we come to see ourselves is partially a reflection of how others see us, hence the idea of the ‚looking glass self”. Autism is a neuro-developmental disorder, characterized by difficulties in social-emotional reciprocity, in nonverbal communicative behaviors used for social interaction, and in the development, preservation and understanding of social interactions. As social interaction is the critical mechanism of development, people diagnosed with Autism are likely to have difficulties in developing their ‚self’. This article suggests a CBT oriented peer group for individuals with autism, in order to help connecting the ‚self’ puzzle.